Sustaining quality in the community: trends in the performance of a structured diabetes care programme in primary care over 16 years. Issue 8 (11th May 2018) - Riordan, F.; McHugh, S. M.; Harkins, V.; Marsden, P.; Kearney, P. M.
Abstract: Aim: To examine the quality of care delivered by a structured primary care‐led programme for people with Type 2 diabetes mellitus in 1999–2016. Methods: The Midland Diabetes Structured Care Programme provides structured primary care‐led management. Trends over time in care processes were examined (using a chi‐squared trend test and age‐ and gender‐adjusted logistic regression). Screening and annual review attendance were reviewed. A composite of eight National Institute for Health and Care Excellence‐recommended processes was used as a quality indicator. Participants who were referred to diabetes nurse specialists were compared with those not referred (Student's t‐ test, Pearson's chi‐squared test, Wilcoxon–Mann–Whitney test). Proportions achieving outcome targets [HbA1c ≤58 mmol/mol (7.5%), blood pressure ≤140/80 mmHg, cholesterol <5.0 mmol/l] were calculated. Results: Data were available for people with diabetes aged ≥18 years: 1998/1999 ( n =336); 2003 ( n =843); 2008 ( n =988); and 2016 ( n =1029). Recording of some processes improved significantly over time (HbA1c, cholesterol, blood pressure, creatinine), and in 2016 exceeded 97%. Foot assessment and annual review attendance declined. In 2016, only 29% of participants had all eight National Institute for Health and Care Excellence processes recorded. A higher proportion of people with diabetes who were referred to a diabetes nurse specialist had poor glycaemic control compared with those not referred. The proportions meeting blood pressure and lipid targets increased over time. Conclusions: Structured primary care led to improvements in the quality of care over time. Poorer recording of some processes, a decline in annual review attendance, and participants remaining at high risk suggest limits to what structured care alone can achieve. Engagement in continuous quality improvement to target other factors, including attendance and self‐management, may deliver further improvements. What's new?: Most studies on the impact of multifaceted, structured, primary care programmes on the quality of diabetes care have a short follow‐up time; studies demonstrating long‐term sustainability are lacking. We found significant improvements in quality of care (care processes delivered) among practices enrolled in a primary care programme over a 16‐year period. Lifestyle processes were less well recorded, and there were declines in foot assessment and attendance at annual review, and participants continued to have poor risk factor control. Programmes may be limited when operating within the constraints of primary care and the wider service context.